A SILENT THREAT: VERY LATE STENT THROMBOSIS IN BARE METAL STENTS AFTER A DECADE - Laksono, Sidhi; Zheng, Tonny; Angkasa, Irwan Surya (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Very late stent thrombosis (VLST) in bare-metal stents (BMS) is a rare but potentially life-threatening complication occurring more than one year after stent implantation. Traditionally, BMS were believed to achieve full endothelialization within months, thereby minimizing late thrombotic risk. However, emerging evidence highlights mechanisms such as neoatherosclerosis and neointimal proliferation as key contributors to VLST, which can present as acute coronary syndrome even many years post-implantation. We report on a 76-year-old male with a history of percutaneous coronary intervention (PCI) using a BMS in the left anterior descending artery (LAD) 10 years prior. He presented with sudden severe chest pain, nausea, and diaphoresis. Electrocardiography revealed an ST-segment elevation myocardial infarction (STEMI) in the inferior-anterior leads. Emergency coronary angiography demonstrated very late thrombosis within the BMS segment of the LAD, accompanied by significant in-stent restenosis. The patient underwent successful primary PCI with the implantation of a new drug-eluting stent overlapping the previous stent, restoring TIMI 3 flow. Notably, risk factors included advanced age, chronic kidney disease, active smoking, and dyslipidemia, despite the patient maintaining daily aspirin therapy. This case underscores that VLST in BMS, although uncommon, remains a critical cause of late myocardial infarction, primarily driven by neoatherosclerosis and neointimal changes within the stented segment. Prompt recognition and emergent PCI can achieve favorable outcomes. Moreover, continuous secondary prevention with long-term antiplatelet therapy and aggressive risk-factor modification is essential to mitigate the risk of VLST, even many years after initial stent placement. Ongoing vigilance is warranted in managing patients with historic BMS to improve prognosis and prevent fatal events.